Formulation and Evaluation of Anti-Aging Cream From Bakuchiol and Moringa Extract - H. J. Dhongade,; Prajakta Hage,; Shubhangi Ugale,; Aishwarya Dalvi, (Asian Journal of Pharmaceutical Research and Development, 2025)
Skin aging is influenced by both intrinsic factors (like age and genetics) and extrinsic factors (like UV exposure and pollution). Conventional treatments such as retinoids are effective but may cause irritation or are unsuitable for pregnant women. Recent studies highlight the anti-aging potential of plant-derived compounds like Bakuchiol and Moringa. This study focuses on developing and evaluating a natural anti-aging cream made from herbal ingredients Bakuchiol ethanolic extract, Moringa oleifera ethanolic extract, and green tea (Camelliasinensis) decoction. With the growing interest in plant-based skincare, the aim of this research was to create a safe, effective, and non-irritating alternative to chemical-based anti-aging products. Bakuchiol, known as a gentle substitute for retinol, helps improve collagen production and reduce wrinkles without causing redness or dryness. Moringaextract is packed with skin-repairing nutrients like polyphenols and vitamins, and greentea contributes antioxidant and anti-inflammatory benefits that soothe and protect the skin. The extracts were obtained using simple and traditional methods—maceration for Bakuchiol and Moringa, and decoction for green tea. The cream was prepared using standard emulsification techniques with cosmetic ingredients like stearic acid, cetyl alcohol, glycerin, and light liquid paraffin. It was then evaluated for physical properties such as pH, appearance, spreadability, viscosity, and stability. The results showed that the cream had a skin-friendly pH (5.5–5.7), remained stable over a month, and had good texture and ease of application with no phase separation or color change. Overall, this herbal cream showed promising results in reducing signs of aging like fine lines and dullness, supporting its potential as a natural, effective anti-aging skincare product.